Contracaecum sp. parasitizing Acestrorhynchus lacustris as a bioindicator for metal pollution in the Batalha River, southeast Brazil - Leite, Lucas A.R.; Pedro, Natacha H.O. [UNESP]; Azevedo, Rodney K. de; Kinoshita, Angela; Gennari, Roseli F.; Watanabe, Shigueo; Abdallah, Vanessa D. (My University, 2017)
Pollution in aquatic ecosystems due to negative human activities remains a problem in both freshwater and marine environments and is an ongoing subject of research. Several studies have shown that some fish parasites can be used as a tool for biomonitoring because they demonstrate higher metal accumulation capacity compared to their host tissues. However, compared to acanthocephalans, information regarding the absorption mechanisms and accumulation rates in nematodes is relatively limited. Here, we evaluated the potential of larvae Contracaecum sp. (L3) as indicators of contamination by metals by analyzing thirteen element concentrations: magnesium (Mg), aluminum (Al), titanium (Ti), chromium (Cr), manganese (Mn), iron (Fe), nickel (Ni), copper (Cu), zinc (Zn), arsenic (As), cadmium (Cd), barium (Ba), and lead (Pb) in the parasites and host Acestrorhynchus lacustris, using inductively coupled plasma mass spectrometry. Twelve of the thirteen analyzed elements were detected in at least 2-fold higher concentrations (e.g. Ni) and were up to approximately 50-fold higher (e.g. Pb) in parasites than in host tissues, including elements known for their high toxicity (As, Cd, Pb) and those considered to be essential (Cu and Zn). Our results suggest that Contracaecum sp. larvae can be used as bioindicators of metal contamination because even in early stages of development, numerous essential and non-essential elements were accumulated, making this system a useful tool for monitoring polluted environments.
Keywords: Biomonitoring; Heavy metals; Inductively coupled plasma mass spectrometry; Larvae nematode; Tietê-Batalha River basin